The remains of Malassez, life and fate in the odontogenic tissues. A review of the literature - Medina Ocampo, Paola Elena (2020)
Epithelial rests of Malassez are cells that are arranged in a network located around the roots of the teeth forming part of the periodontal ligament tissues. The functions that these cells perform are not very specific, however, they have shown to participate in the maintenance of the periodontal ligament space, regeneration of periodontal tissue, including cement regeneration among others. In addition, they are able to differentiate into other cell lineages, thereby demonstrating their capacity as stem cells. These cells are best known for their role in the participation and proliferation of the formation of different pathologies, such as cysts and odontogenic tumors.